Vacancies in Metal−Organic Frameworks: Formation, Arrangement, and Functions. Issue 5 (5th February 2022) - Pang, Qingqing; Yang, Lingyi; Li, Qiaowei
Abstract : Vacancies in crystalline materials are missing single atoms and missing clusters of atoms in the ordered lattice. In reticular structures such as metal−organic frameworks (MOFs), vacancy can exist in the form of organic linker vacancy, inorganic cluster vacancy, and macroscopic vacancy. In last decade, extensive researches have been developed in exploring the formation, arrangement, and functions of vacancies in MOFs. In this review, an overview of progress in introducing structural vacancies into MOFs either by de novo synthesis or by postsynthetic modification is provided. Different spatial arrangements of vacancies (random, site‐selective, and correlated/ordered) are also highlighted, with an emphasis on new synthetic strategies and mechanisms, and advanced characterization methods needed to control vacancies in a sophisticated manner. Furthermore, enhanced gas adsorption, precise framework grafting, and efficient molecular conversion empowered by vacancies in MOFs are summarized. Future opportunities in this field are envisioned by considering vacancies as a new kind of constituents to reshape the MOF backbone and pores for higher structural complexities and tailored functions. Abstract : Vacancies have become an important player in the design and functions of metal−organic frameworks. Prominent examples of vacancies with different formation methods (de novo synthesis and postsyntheic modification), various arrangements (random, site‐selective, and correlated/ordered), and attractive functions (adsorption, grafting, and conversion) are illustrated. Perspectives on vacancies' capability in transforming both the framework backbone and the enclosed space are provided.